Dakwah Perspektif Ekologi Media - khasanah, Siti uswatun (Universitas Islam Negeri Raden Intan Lampung, 2018)
Globalization that occurs today does not necessarily make da'wah in Indonesia can be felt evenly by the community. One of the factors that cause some people to get da'wah opportunity is poverty. In additions there are also other problems such as low audience spirit and quality of d’ii, facilities and infrastructure are not adequate, and the low relevance of da'wah with needs. With the development of technology, ideally da’wah in Indonesia is efficient, effective, has a clear standardization and produce quality output as needed. Da'wah by using technology is something that can not be denied. Theoretically, McLuhan (1964) states that we have a symbiotic relationship with technology that uses media. Man creates technology, and instead technology makes man. The theory of media ecology has the assumption that: 1). Media encompasses every action in society, 2). Media improves our perceptions and organizes experiences, 3). The media brings the whole world together. Communication technology has a great effect on people's lives (especially da'wah). Almost all human activities and actions can not be separated from the influence of technology. Then it should be used wisely by the Muslim community. With quality education is expected to prepare people to face this global era.